In Other News: The Significance of Canadian Media Sources in an Analysis of Local Music Collection Literature - Kmiech, Veronica (CAML Review / Revue de l’ACBM, 2018)
Music libraries have an important role in preserving and providing access to local music materials for scholarly and general audiences. This paper is based on research carried out as part of the “Regional Music Collections” project (led by Carolyn Doi, University of Saskatchewan, and now entitled “Sounds of Home: Exploring Local Music Collections and Collecting in Canada”). During this portion of the project, we conducted a qualitative systematic review and thematic analysis of the literature on local music collections. The paper will provide a brief description of the literature review process and content analysis, followed by a more detailed exploration of eight Canadian newspaper articles. In exploring the articles, NVivo software was used to identify three potential themes: new, copyright, and free. The goal of this paper is to see if these themes can aid in identifying what Canadian media sources say about local music collections, what the relationships are between a community and such a collection, and how Canadian media sources might inform practices for managing collections of local music.